Young Positive Schema Questionnaire (YPSQ): Psychometric properties and factor structure of Persian version in female students - Didevar, Roya; Zarqam, Elham; Andalib Kourayem, Morteza (Applied Family Therapy Journal (AFTJ), 2022)
Aim: Due to the lack of a Persian version of the present instrument, the present study examined the psychometric properties and functional structure of the Young Positive Schema Questionnaire in female students of the Islamic Azad University of Varamin. Methods: The present study was descriptive-applied research with field method. Data collection tools included Young Lewis et al. (2018) positive schema questionnaire, the short form of Young Wilburne et al. (2002) schema questionnaire, Loveband Depression and Anxiety and Stress Scale (1995) and Young and Parenting Questionnaire. Et al. (2003). To evaluate the face and content validity of the opinion of 11 experts in the field of psychology and to evaluate the construct validity and internal reliability of 468 samples, for divergent validity of 135 samples and to evaluate the retest reliability of the data of 100 samples were analyzed. In this study, content validity method (CVR) and content validity index (CVI) were used to calculate content validity. In order to evaluate the internal reliability of the questionnaire, Cronbach's alpha method was used and in order to evaluate the time reliability of the retest method, divergent validity of Pearson correlation with SPSS software was used. Confirmatory factor analysis with LISREL software was used to evaluate the construct validity. Results: The results showed that the 76-item model with 17 factors was approved. Pearson correlation coefficient between the scores obtained from the two performances ranged from 0.68 to 0.87 and all were significant (P